Peran sumber daya manusia (SDM) dalam perkembangan perbankan syariah: sebuah analisis kualitas dan kinerja pegawai - nilam sari; Abrar Amri (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2018)
Human resources have a very important role in a company organization especially when compared to other resources. Employee performance is a very important thing in an effort to achieve change in order to achieve its goals. This study discusses the influence of the quality of human resources on the performance of sharia banking employees in Aceh and how efforts should be made in improving the quality of sharia banking human resources in Aceh. The research method used is a mixed method (Mixed Method). Based on test variables obtained by tcount of 3.859 while t table of 2.048 the results of this calculation indicate that tcount t table with a significance level of 0.001 or probability above α = 5%. Thus the results of statistical calculations indicate that the variable quality of human resources has a significant influence on employee performance. Which means that the higher the quality of human resources, the higher the performance of employees in Islamic banking. Efforts to improve the quality of banking Human Resources can be done through: 1) Evaluation of a sustainable Islamic economic curriculum in higher education institutions. 2) Establish a faculty / Islamic economic study program in accordance with the needs of the Islamic banking market. 3) Higher Education collaborates with Bank Indonesia to carry out Islamic economic education and training for students and employees of Islamic banks. 5) Education and training on banking to improve the quality of human resources in sharia banking is a short-term effort that can be done now. While the efforts made in the long term are by organizing education that is synergized between the education provider (college) user (bank) and the person in charge of education (government).